Nurses’ characteristics and spiritual care knowledge in hospital setting: A cross-sectional study - Nuridah, Nuridah; Yodang, Yodang (The Journal of Palembang Nursing Studies, 2024)
Background: The low awareness among nurses regarding the provision of spiritual services in healthcare settings results in unmet spiritual needs among patients, leading hospitals to be perceived solely as centers focusing on physical aspects. This stems from nurses’ low competence in providing spiritual care services. Objective: This study aims to analyze the correlation between nurses’ characteristics and their knowledge of spiritual care in a hospital setting. Methods: A retrospective cross-sectional study was conducted, with respondents recruited using a purposive sampling technique. Inclusion criteria included nurses working in hospitals who directly care for patients. Data were analyzed using univariate analysis (frequency and percentage) and bivariate analysis using Fisher’s exact test.  Result: A total of 117 nurses participated in this study, of whom 59.8% were female, 63.25% were aged <31 years old, 77.8% were permanent workers, 57.2% had work experience < 5 years, 91.5% were Muslim, 55.6% attended workshops/seminars, and 76.9% had moderate knowledge. Workshops/seminars had a positive correlation with knowledge and were statistically significant. Conclusion: Spiritual workshops/seminars have a positive correlation and are statistically significant in enhancing nurses’ knowledge of spiritual care in a hospital setting. Therefore, there is a need to improve nurses’ spiritual care knowledge through continuing education, such as training, seminars, or workshops.